PENGARUH FASILITAS BELAJAR DAN MOTIVASI BELAJAR TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN EKONOMI DI MAN 2 BENGKALIS - Octaviani, Sisca; Suarman, Suarman; Syabus, Hardisyem (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract : This research to determine the influence of learning facilities and learning motivation on learning outcomes on economic lesson learning in MAN 2 Bengkalis. The sample in this research is the students of class X IIS and XI IIS that is as many as 42 students. The data collection of this research is documentation an questionnaire. The data analysis of data used is multiple linear analysis. The results showed that learning facilities and learning motivation have a significant effect on the learning outcomes. Seen from the calculation of R2 ( R squere change ) obtained value of 0,418 this mean that the contribution of the influence of learning facilities and learning motivation of learning outcomes is 41,8 %, while the remaining 58,2 % influenced by other variable outside this research.Keywods : Learning facilities, learning motivation, learning outcomes